Measurement of internal diameters of capillaries and glass syringes using gravimetric and optical methods for microflow applications - Batista, Elsa; Álvares, Miguel; Martins, Rui F; Ogheard, Florestan; Geršl, Jan; Godinho, Isabel (Biomedizinische Technik. Biomedical engineering, 2023)
OBJECTIVES: Microflow measurement devices are used in several science and health applications, mainly drug delivery. In the last decade, several new methods based on optical technology were developed, namely the front tracking and interferometric method, in which the knowledge of the inner diameter of the syringe or the capillary used is critical. Only a few National Metrology Institutes (NMIs) can perform inner diameter measurements below 1 mm, which requires expensive technology. Therefore, IPQ, in cooperation with CETIAT, CMI and UNIDEMI, under the EMPIR project 18HLT08 MeDDII - Metrology for Drug Delivery, developed new measurement methods for small inner diameter tubes based on the gravimetric principle and optical methods in order to simplify the apparatus used for this type of measurements without increasing uncertainty. METHODS: The gravimetric experimental setup consists of measuring the liquid volume on a specific length of the glass tube. The optical method used is based on the front track principle that uses a high-resolution camera and ImageJ software, to determine the diameter at both ends of each capillary. RESULTS: To validate the developed methods, a comparison was performed between CETIAT, CMI and IPQ and the results obtained were all consistent. CONCLUSIONS: This work allowed the determination of inner diameter of syringes or capillaries using two different methods with relative expanded uncertainties from 0.1 to 0.5% (k=2), that can be applied for flow measurements using optical technology.
Keywords: Capillaries; optical technology; syringe; Syringes; capillary; microflow; injekční stříkačky; kapiláry; Drug Delivery Systems; gravimetry; lékové transportní systémy